A neglected source of household air pollution: a preliminary, mixed methods study of purposely produced household smoke in Wollo, Ethiopia. (10th December 2020) - Wilkinson, R; Afework, T; Mortimore, A; Phillips, D I W; Willcox, M; Levene, D; Kaba, M
Abstract: Background: Ill health associated with household air pollution (HAP) is increasingly recognized as a public health problem in sub-Saharan Africa. To date, attempts to reduce HAP have focussed on smoke from cooking fires and have ignored traditional cultural practices which generate purposely produced smoke (PPS). This study aimed to investigate PPS prevalence, reasons for use and safety perceptions. Methods: The study was conducted in Wollo, Ethiopia, and used a mixed methods approach of quantitative surveys (analysed descriptively) and qualitative interviews with householders and healthcare workers (analysed thematically). Results: PPS use was reported by 99% of survey respondents and it was considered a fundamental part of life. Although reasons for use included housekeeping, culture/religion and well-being, coffee ceremony was most commonly cited (44% of respondents). Both householders and healthcare workers appeared to assume PPS is safe, except for people with certain underlying conditions. Healthcare workers felt the lack of evidence of harm from PPS meant there was no justification for intervention. Conclusion: This study, the first in-depth study of PPS, has shown its use to be widespread, with many perceived benefits and thus a very important part of local culture in this sample Ethiopian community. Consequently, any public health interventions aimed at reducing HAP in this setting need to consider PPS.